Numerical and Experimental Study on Thermal Damage Induced by Medium—Infrared Laser - Zhenhua Lei; Yubin Zhang; Qingzhi Li; Ting Shao; Laixi Sun; Kaixuan Wang; Zao Yi; Xin Ye; Wanguo Zheng; Pinghui Wu (Photonics, 2022)
We studied the laser-induced thermal damage on the surface of a single crystal silicon mirror illuminated by a mid-infrared intense laser. We used mid−infrared quasi-continuous wave lasers to irradiate the surface of the single−crystal silicon mirror. The power density of the irradiation process is 1 kW/cm2 to 17 kW/cm2, and the transient temperature field and thermal stress field under different laser fluxes were obtained. The simulation results show that we can calculate the thermal stress and temperature under laser irradiation. In addition, irradiance exceeding the corresponding breaking strength and melting point limit was obtained by the model. We can predict the irradiance that causes cracking and melting. There is little difference between experimental results and simulation results. On this basis, the thermal damage to the surface of the silicon wafer caused by continuous mid−infrared laser irradiation was studied.